1986
DOI: 10.1111/j.0954-6820.1986.tb03298.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Reactivity in Diabetes Mellitus

Abstract: ABSTRACT. Seventeen patients with insulin‐dependent diabetes mellitus, all below the age of 45 years, were studied. Five of them had retinopathy but no other micro‐ or macrovascular diabetic complications. None of them had any other concurrent disorder or were on any medication but insulin. The results were compared to those of 17 healthy volunteers of comparable age. There was no difference between the two groups in venous platelet counts, serum production of thromboxane B2 (TXB2), ADP‐induced platelet aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…The curves of the mean aggregate sizes and light transmission characteristics suggested that the rates of collagen-induced aggregation of isolated platelets in MetS patients significantly exceeded the corresponding values in group of healthy volunteers (Idrisova et al, 2007 ). Several publications suggest that platelet sensitivity in T2DM patients increases due to action of the various platelet aggregation inductors including ADP, thrombin, and collagen (Kutti et al, 1986 ; Bode-Böger et al, 1998 ; Tokuda et al, 2012 ). Correlation analysis reveals the presence of direct relationship between the glycated hemoglobin levels and the rates of collagen- and ADP-induced platelet aggregation activities (Rabini et al, 1998 ; Gruzdeva et al, 2008 ; Tokuda et al, 2012 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The curves of the mean aggregate sizes and light transmission characteristics suggested that the rates of collagen-induced aggregation of isolated platelets in MetS patients significantly exceeded the corresponding values in group of healthy volunteers (Idrisova et al, 2007 ). Several publications suggest that platelet sensitivity in T2DM patients increases due to action of the various platelet aggregation inductors including ADP, thrombin, and collagen (Kutti et al, 1986 ; Bode-Böger et al, 1998 ; Tokuda et al, 2012 ). Correlation analysis reveals the presence of direct relationship between the glycated hemoglobin levels and the rates of collagen- and ADP-induced platelet aggregation activities (Rabini et al, 1998 ; Gruzdeva et al, 2008 ; Tokuda et al, 2012 ).…”
mentioning
confidence: 99%
“…Increased glycosylation of platelet proteins modulates cellular functions in diabetes. In particular, possible glycosylation of calmodulin that modulates activity of nitric oxide synthase (NOS) results in the decreased synthesis of nitric oxide (NO) (Kutti et al, 1986 ).…”
mentioning
confidence: 99%
“…Various mechanisms have been suggested to be responsible for this enhanced platelet activation and aggregation such as abnormal Ca 2+ -ATPase activity (Rosado et al, 2004;Jardin et al, 2006), impaired Ca 2+ homeostasis (Ishii et al, 1991), impairment in platelet signalling such as nitric oxide (NO) production (Trovati and Anfossi, 2002). However, in vitro studies by Kutti et al (1986) showed no increase in adenosine diphosphate (ADP) sensitivity of platelet from diabetic patients. According to Malik et al (2012), the reason for the contrasting result could be the fact that all the patients in the study by Kutti et al (1986) were insulin dependent diabetics.…”
Section: Resultsmentioning
confidence: 99%
“…However, in vitro studies by Kutti et al (1986) showed no increase in adenosine diphosphate (ADP) sensitivity of platelet from diabetic patients. According to Malik et al (2012), the reason for the contrasting result could be the fact that all the patients in the study by Kutti et al (1986) were insulin dependent diabetics. And as described by Harrison and his colleague (1980), chronic use of insulin administration may restore prostacyclin PGI2 production in platelets of diabetic animals leading to a decrease in their aggregation tendency.…”
Section: Resultsmentioning
confidence: 99%
“…In the patient with diabetes, anti-aggregatory mechanisms in the endothelium are impaired (Ceriello 2004). Platelets are more susceptible to activation and aggregation (Kutti 1986) and antifibrinolytic activity is attenuated (Colwell 2003).…”
Section: Diabetes Cardiovascular Disease and The Role Of Plateletsmentioning
confidence: 99%